Physical Activity and Television Watching Duration in Relation to Blood Pressure of School-Aged Children - Ayu Nur Hidayah; Khoiril Anam; Pajri Mughni Alim; Nanang Indardi; Anies Setiowati (Newinera Publisher, 2026)
Hypertension in children is a serious threat due to a sedentary modern lifestyle. Low physical activity and high screen time are strongly suspected to be risk factors for increased blood pressure. Objective: To analyze the relationship between physical activity levels and television viewing/lying down duration with blood pressure in school-aged children in Mluweh Village. Methods: This observational study involved 105 students (6-17 years old) selected by total sampling. Blood pressure was classified based on the 2017 AAP Clinical Practice Guideline standards. Physical activity and television viewing/lying down duration were measured using a modified GPAQ questionnaire. Data were analyzed using the Chi-Square test (α = 0.05). Results: The majority of respondents had light physical activity (64.7%) and high television viewing/lying down duration (94.3%). Statistical analysis showed no significant relationship between physical activity levels and blood pressure (p = 0.814). However, a statistically significant relationship was found between television viewing/lying down duration and blood pressure (p = 0.027). Conclusion: High television viewing/lying down time exceeding 2 hours per day is a strong predictor of increased blood pressure in children. Limiting screen time from an early age is necessary to minimize the risk of long-term cardiovascular disorders.